IMPLEMENTASI ALGORITMA FISHER-YATES SHUFFLE PADA SISTEM UJIAN ONLINE BERBASIS WEBSITE DI SMP SWASTA IR. H. DJUANDA TEBING TINGGI - Muhammad Fauzan Lubis; Antoni; Rachmat Aulia (Jurnal Riset Multidisiplin Edukasi, 2025)
Digital transformation in education has been rapidly advancing, particularly in online exam systems implemented at SMP Swasta Ir. H. Djuanda Tebing Tinggi. One of the main challenges in online exams is the potential for cheating, which can arise due to the identical order of questions among participants. To address this issue, this research implements the Fisher-Yates Shuffle algorithm, aimed at randomizing the order of questions and answers in a fair and consistent manner. The results show that the implementation of this algorithm reduces the possibility of collusion and cheating among students. The online exam system developed using PHP, MySQL, and XAMPP successfully enhances fairness in the exam, ensuring that each student receives a different question order. This study contributes to the development of a fairer and more efficient online exam system, while also improving the student user experience.